2016
DOI: 10.1039/c5ra27971b
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyester and its sodium titanate nanocomposites as proton exchange membranes for fuel cells

Abstract: Sulfonated hyperbranched polyesters and their hybrids with sodium titanate nanowire were used to prepare novel proton exchange membranes for fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The assembly of the bulky hyperbranched structure and the linear structure protects the backbone and quaternary ammonium groups from the OH − attack through the steric hindrance effect. The result showed that chemically stable Q-PAES/PPO-XY blended membranes were obtained [ 31 , 33 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly of the bulky hyperbranched structure and the linear structure protects the backbone and quaternary ammonium groups from the OH − attack through the steric hindrance effect. The result showed that chemically stable Q-PAES/PPO-XY blended membranes were obtained [ 31 , 33 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Novel hyperbranched anion exchange membranes (HBAEMs) are promising backbone structures for AEMs that have been reported to possess improved dimensional stability, alkaline stability, and clear micro-phase separation of hydrophilic/hydrophobic domains, which result in excellent ionic conductivity and high solubility enabling facile membrane fabrication and reprocessing compared to other polymers [ 29 , 30 , 31 , 32 ]. Ge et al [ 33 ] reported hyperbranched poly-4-(chloromethyl) styrene (HB-PVBC) AEMs with superior dimensional stability and an ionic conductivity of 123.01 mS cm −1 at 80 °C, which results from the well-separated hydrophilic/hydrophobic microphases and the low swelling ratio of HB-PVBC due to its hyperbranched structure.…”
Section: Introductionmentioning
confidence: 99%
“…PES/PESAM lm was prepared by phase inversion method. 24 Particularly, equal weight ratio of the synthesized PESAM and PES were dissolved in NMP as a solvent. The polymer: solvent ratio was 20 : 80 and the polymers solution was le for 24 h under vigorous stirring.…”
Section: Preparation Of Polyethersulfone/hyperbranched Polyester Amidmentioning
confidence: 99%
“…Membrane preparation with high selectivity and high permeability are necessary in the most applications especially in water desalination [1][2][3][4]. on by Generally, in membrane technology, the membrane performance (selectivity and permeability) depends on the membrane structure and membrane material [5][6][7][8]. Wet phase inversion process is a significant method for membrane preparation.…”
Section: Introductionmentioning
confidence: 99%